Eksisi Intralesi sebagai Strategi Tatalaksana Keloid: Laporan Kasus Berbasis Bukti - Trimartani, T.; Widodo, Dini Widiarni; Ranakusuma, Respati Wulansari; M, Mesiwisani; Putri, Annisa; Reksodiputro, Mirta Hediyati (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Several therapeutic modalities exist for keloids, but management them remains a challenge due to high recurrence rates. These case series discussed surgical therapy using intralesional excision. Purpose: To compare the effect of intralesional excision with extra-lesional excision followed by post-operative triamcinolone injection, on the recurrence rates of auricular keloids. Case reports: Three patients with keloids treated with intralesional excision were presented. The first patient, a 20-year- old male, had keloids on both ears, nose, hands, and feet following burnt injury. The second patient, a 19-year-old female, had a keloid lump on the left auricle. The patient had a history of bilateral microtia and had undergone stage 1 auriculoplasty with rib grafting on both ears. The third patient, a 36-year-old woman with complaints of a keloid appearing for 3 years in the helix of her right ear, and underwent surgical excision followed by triamcinolone injection. Clinical question: How does the recurrence in patients with auricular keloid undergoing intralesional excision and postoperative triamcinolone injection, compared to extra-lesional excision and triamcinolone injection? Method: A systematic literature search was conducted using PubMed, Cochrane Library, Scopus, and ClinicalKey with relevant keywords: “intralesional excision”, AND “keloid”. Result: A total of 192 articles were found, and 3 articles met the eligibility criteria. Conclusion: The literature search revealed no difference in the recurrence rates between intralesional and extra-lesional excision with triamcinolone injection. Further research on this topic is needed. Keywords: intralesional excision, keloid, recurrence